Derecho PUC: Fifteen Years of Legal History (1987-2003) - Ramos Núñez, Carlos (2004)
The journal Derecho of the Pontificia Universidad Católica del Perú has been a transcendent tool for the advancement of legal thought and research since its establishment in 1944. It has benefited both the student and teaching communities. Its contributions have transcended the university campus, influencing Peruvian legal thought from the 20th century to the beginning of the 21st century. This paper seeks to commemorate the editorial trajectory and evolution of the journal, focusing on the period from issue 41 (December 1987) to issue 56 (December 2003). As can be observed, throughout its history, Derecho PUC has been able to identify and reflect the prevailing trends, methodologies, and approaches within the context of the country's legal discourse, thereby adapting to the social and legal changes that have shaped national history.